Pengujian Koalisi Likuiditas, Solvabilitas dan Profitabilitas Terhadap Harga Saham (Perusahaan Sektor Pertanian Terdaftar di ISSI) - Sri Delasmi Jayanti; Lidia Desiana; Aryanti Aryanti (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2017)
This research was aimed to find out the coalition liquidity, solvency, and profitability testing of stock prices. The population in this research was agricultural companies listed in the ISSI registered in the period 2013-2016 as many as 14 companies. The sample used in this research were only six companies by using sampling technique based on purposive sampling. The results showed that the variables CR, and DAR partially had no significant effect on stock prices. For ROE variable partially had a significant positive effect on stock price. While the simultaneous variables CR, DAR, and ROE had significant influences on stock prices. And based on test results, determination coefficient showed that Adjusted R2 value in regression model of 47% while the remaining 53% was influenced by other factors not included in the regression model.